1979
DOI: 10.1002/ijc.2910230307
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon hydroxylase inducibility is not altered in bladder cancer patients or their progeny

Abstract: We investigated the possible influence of aryl hydrocarbon hydroxylase (AHH) on susceptibility to bladder cancer in humans. AHH inducibility was measured in the cultured lymphocytes of 16 patients who were being followed after successful treatment for bladder cancer, in 53 progeny of bladder cancer patients, and in matched controls. In both the progeny and patient populations, no evidence was found for a difference between the distribution of AHH inducibility or induced AHH activity compared to the distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The formalin-fixed hearts were embedded in gelatin and sectioned on a cryostat as described (10,13). The number of oil red Q staining lesions was counted in a standardized region of the aorta as described (13).…”
Section: Methodsmentioning
confidence: 99%
“…The formalin-fixed hearts were embedded in gelatin and sectioned on a cryostat as described (10,13). The number of oil red Q staining lesions was counted in a standardized region of the aorta as described (13).…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the ease of genetic and physical manipulation of mice, mice are the most popular animal models of atherosclerosis. One of the first models of atherosclerosis in mice was the hypercholesterolemia model developed by Paigen et al [101104]. It was found that only the C57BL/6J strain could develop atherosclerosis if hypercholesterolemia was induced by genetic mutation and high-fat diet.…”
Section: Atherosclerosis and The Endotheliummentioning
confidence: 99%